2015
DOI: 10.1126/science.aab0696
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of monoterpene scent compounds in roses

Abstract: The scent of roses (Rosa x hybrida) is composed of hundreds of volatile molecules. Monoterpenes represent up to 70% percent of the scent content in some cultivars, such as the Papa Meilland rose. Monoterpene biosynthesis in plants relies on plastid-localized terpene synthases. Combining transcriptomic and genetic approaches, we show that the Nudix hydrolase RhNUDX1, localized in the cytoplasm, is part of a pathway for the biosynthesis of free monoterpene alcohols that contribute to fragrance in roses. The RhNU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
203
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(210 citation statements)
references
References 44 publications
(32 reference statements)
1
203
1
5
Order By: Relevance
“…The conversion of CDP to trans-chrysanthemol could be catalyzed by a member of the terpene synthase family similar to those terpene synthases catalyzing the conversion of geranyl diphosphate to the alcohol monoterpenes geraniol and linalool in many species (Chen et al, 2011), or CDP could be hydrolyzed by phosphatases to give trans-chrysanthemol, similar to the conversion of geranyl diphosphate to geraniol in rose (Rosa spp.) flowers (Magnard et al, 2015). However, no such enzymatic activities were reported thus far in T. cinerariifolium.…”
mentioning
confidence: 93%
“…The conversion of CDP to trans-chrysanthemol could be catalyzed by a member of the terpene synthase family similar to those terpene synthases catalyzing the conversion of geranyl diphosphate to the alcohol monoterpenes geraniol and linalool in many species (Chen et al, 2011), or CDP could be hydrolyzed by phosphatases to give trans-chrysanthemol, similar to the conversion of geranyl diphosphate to geraniol in rose (Rosa spp.) flowers (Magnard et al, 2015). However, no such enzymatic activities were reported thus far in T. cinerariifolium.…”
mentioning
confidence: 93%
“…The corresponding probe belongs to cluster 4, which also harbors several monoterpenes (Table 2, Supplementary Tables S8, S9). Recently, a rose nudix hydrolase was reported to convert geranyl diphosphate to geranyl monophosphate, which in turn is hydrolyzed to geraniol by a phosphatase activity (Magnard et al, 2015). This alternative and completely new terpene synthase-independent route for monoterpene production might play a role also in other plants, including grapevine.…”
Section: Resultsmentioning
confidence: 99%
“…The length of time required for effective silencing of flowers with graft‐accelerated VIGS (approximately 30–35 d) is also much shorter compared with the conventional method (approximately 90–270 d; Figure ). Using the grafting method, genes related to floral color ( RhDFR1 (Suzuki et al ; Katsumoto et al )), development ( RhAG (Ma et al )), and fragrance ( RhNUDX1 (Magnard et al )) were successfully silenced. We found that 44.4% of RhDFR1 ‐silenced rose flowers exhibited bleached petals.…”
Section: Discussionmentioning
confidence: 99%